Pengembangan Media Pembelajaran Berbasis Auto Cad pada Materi Bangun Ruang Sisi Datar di Kelas VIII SMPN 9 Kubung - Kurniawan, Martino; Oktavinora, Rita; Zaimil, Roza (Indo-MathEdu Intellectuals Journal, 2025)
This research was motivated by several things, namely students' lack of interest in learning mathematics, students felt lazy to pay attention when educators explained the material, the learning media used were only worksheets and Auto CAD media had never been used in school. This research aims to find out whether the development of Auto CAD Media on flat-sided building material in class VIII SMPN 9 Kubung is valid? This research is in the form of Research and Depolotment (R&D) research using the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The research instrument is a validation questionnaire for material expert 1, material expert 2 and media expert. The data produced is analyzed quantitatively and qualitatively. Validation was carried out by 3 validators, namely 2 material experts and 1 media expert. Based on the research results, it is known that validation of material expert 1 received an average of 91%, validation of material expert 2 was 77% and validation of media experts was 84% ​​with an overall average of 84% in the very valid category. The conclusion of this research is to produce Auto CAD Media for flat-sided spatial structures in class VIII of SMPN 9 Kubung with a very valid category.